An empirical study on students' behaviour regarding creative accounting techniques - Diana Elisabeta BALACIU; Lucian CERNUŞCA; Ioana Teodora MEŞTER (Institute of Economic Research (IER), 2015)
The scope of this study is to investigate the accounting master students' attitude and perception regarding ethics and the existence and manifestations of creative accounting, in the context of harmonization of the Romanian accounting system. The sample of our research consists of accounting master student from three Romanian representative universities. Our survey regarding the students' perception on the accounting practices is a descriptive one, we have used as an instrument of research the questionnaire. These were posted on an Internet page and also, we used the possibility of its direct approach, preserving the anonymity of the respondent. In order to attain our research's objectives we have first presented a descriptive analysis of the answers, but tested some research propositions from a practical point of view as well. These show that there is a correlation between the master students' tendency (as potential managers) to modify the accounting information and to distort the real image of financial reports and their ethical behaviour. We consider our study is valuable and attractive from the perspective of the elements of introspection and connection that it detects, in the context of a clear interest expressed by the authors in the students' psychology and their irrational behaviour regarding their potential future decisions.
Keywords: M41; 330; Creative accounting; ethics; risk propensity; student behaviour; International Financial Reporting Standards